Abundance of benthic foraminifera in the late Oligocene-Neogene in ODP Holes 121-752A, 183-1139A and 189-1168A - Dana Ridha; Ian Boomer; Kirsty M Edgar (PANGAEA, 2020)
Count data for most abundant benthic foraminifera in the late Oligocene-Neogene in ODP Holes 752A, 1139A and 1139A
Supplement to: Ridha, D et al. (2019): Latest Oligocene to earliest Pliocene deep-sea benthic foraminifera from Ocean Drilling Program (ODP) Sites 752, 1168 and 1139, southern Indian Ocean. Journal of Micropalaeontology, 38(2), 189-229, https://doi.org/10.5194/jm-38-189-2019